The Effect of Problem Based Learning and Open-Ended Learning on Mathematics Creative Thinking Ability: A Meta Analysis Study - Kurniati, Nia; Sutiarso, Sugeng (Jurnal Pendidikan MIPA, 2021)
This study aims to analyze the effect of Problem Based Learning (PBL) and Open Ended Learning (OEL) on the ability to think creative mathematically based on the effect size category, education level, and learning materials. This research method is a meta-analysis by reviewing several journals that have been published online. This study used 15 journals on PBL and 15 journals on OEL related to mathematical creative thinking skills. The instrument in this meta-analysis was carried out with a coding category sheet according to the research variables, namely: the year of the study, the title of the study, the level of education, the material used in the study, also the independent variable and dependent variable of study. The data analysis technique used is descriptive statistics. The results of the meta-analysis showed that PBL had a higher effect than OEL on students' mathematical creative thinking abilities. Based on the level of education, PBL has more influence on junior high school students, while OEL has more influence on students at high school level. In terms of learning materials, PBL has more influence on SPLDV material than other materials, while OEL has more influence on social arithmetic material. Keywords: mathematical creative thinking ability, meta analysis, Open-Ended Learning, Problem Based Learning. DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp112-120